Pengaruh Asap Rokok, Pendapatan Dan Kepadatan Anggota Keluarga Terhadap Kejadian Infeksi Saluran Pernapasan Akut (ISPA) Pada Balita - Triyana, Novi; Wijaya, Adi; Solehudin, Solehudin (JIMAD : Jurnal Ilmiah Multidisiplin, 2024)
Upper Respiratory Tract Infection is an acute infection that attacks the upper respiratory tract and lower respiratory tract. Viruses, fungi and bacteria are the causes of this infection. The general aim of this research is to determine the effect of cigarette smoke, income and density of family members on the incidence of acute respiratory infections in toddlers at the Dramaga Community Health Center. This research uses a quantitative study with a descriptive correlation design with a cross sectional approach. The population in this study was 70 respondents with a sample of 58 respondents. The study uses univariate, bivariate and multivariate analysis using Spearman correlation and regression tests. The instrument used was a questionnaire. Based on the results of bivariate analysis, the p-value is 0.000 < smaller than 0.05, there is a significant relationship between cigarette smoke and the incidence of ISPA, the p-value is 0.021 < smaller than 0.05, there is a significant relationship between income and the incidence of ISPA, the value p-value 0.000 < smaller than 0.05, there is a significant relationship between the density of family members and the incidence of ARI. The research conclusion is that cigarette smoke, income and density of family members influence the incidence of ISPA in toddlers